The Interaction of Ecology and Computing and its Ethical Consequences - Marlowe, Thomas J. (Theology and science, 2025)
The interaction of ecology and science is clear; that with computing, much less so, other than as an analytic tool. But increasingly severe overconsumption of natural resources, primarily power and water, by applications, including generative artificial intelligence, very large databases and data analytics, and cryptocurrency, presents a serious ethical challenge. In specific instances, this may be balanced, ethically and practically, by the good achieved, especially for environmental issues. Even then, local concerns arise, such as environmental racism. In this paper, we apply Catholic Social Teaching (CST) and other traditions and provide recommendations for ethical use of these technologies.